Intellectual disability and patient activation after release from prison: a prospective cohort study - Young, J.; Cumming, C.; van Dooren, K.; Lennox, N.; Alati, Rosa; Spittal, M.; Brophy, L.; Preen, D.; Kinner, S. (Wiley-Blackwell Publishing Ltd, 2017)
© 2017 MENCAP and International Association of the Scientific Study of Intellectual and Developmental Disabilities and John Wiley & Sons Ltd Background: Intellectual disability and patient activation may be important drivers of inequities in health service access and health outcomes for people with intellectual disability transitioning from prison to the community. We assessed the association between intellectual disability and patient activation after prison release and examined whether this association varied, depending on whether intellectual disability was identified prior to prison release. Methods: Overall, 936 prisoners were screened for intellectual disability by using the Hayes Ability Screening Index and completed the Patient Activation Measure (PAM) within 6 weeks of prison release and again at 1, 3 and 6 months post-release. We estimated the association between intellectual disability status and PAM scores by using a multilevel linear model, adjusting for sociodemographic, behavioural, health and criminogenic factors. We used propensity score matching to estimate the impact of being identified with intellectual disability prior to release from prison on the change in mean PAM score after prison release. Results: Compared with those who screened negative for intellectual disability, ex-prisoners who screened positive, both with and without prior identification of intellectual disability, had significantly decreased mean PAM scores [(B = -4.3; 95% CI: -6.3, -2.4) and (B = -4.5; 95% CI: -6.8, -2.3), respectively] over 6 months of follow-up. Among those who reported being identified with intellectual disability prior to release from prison, a significant increase in PAM score at the 6-month follow-up interview (B = 5.89; 95% CI: 2.35, 9.42; P = 0.001) was attributable to being identified with intellectual disability prior to release. Conclusions: Ex-prisoners screening positive for possible intellectual disability have decreased patient activation for at least 6 months after release from prison. However, individuals whose possible intellectual disability is unidentified appear to be particularly vulnerable. Incarceration is a pivotal opportunity for the identification of intellectual disability and for initiating transitional linkages to health and intellectual disability-specific community services for this marginalised population.